Perspektiven von Schüler:innen in der designbasierten Forschung - Drepper, Laura; Hoffmann, Johanna (EDeR. Educational Design Research)
m Beitrag werden Ergebnisse der Design-Based-Research-Studie Studierende als Lesecoaches dargestellt, in der das Lernsetting Lesen mit Rätseln zum Lesenlernen im 3./4. Schuljahr entwickelt wurde. Dieses zeichnet sich durch eine mehrdimensionale, adaptive und kindorientierte Ausrichtung aus. In den Fokus wird die Perspektive von Schüler:innen genommen, die das Lernsetting über zehn Wochen erprobt haben. Ausgehend von qualitativen Leitfadeninterviews mit einer Teilstichprobe (n=12) beurteilen die Kinder die Rätselaufgaben, die Arbeit mit einem anderen Kind und die Arbeit mit einem digitalen Audiostift. Im Sinne der designbasierten Forschung werden aus den Beurteilungen der Kinder Gestaltungsprinzipien zur Weiterentwicklung des Lernsettings abgeleitet. Die Ergebnisse zeigen, dass die Perspektive der Schüler:innen in der designbasierten Forschung eine Bereicherung darstellen kann.

Deutschlehrkräfte als Co-Designer in der designbasierten Forschung. Wie Theorie und Praxis den Deutschunterricht weiterentwickeln - Drepper, Laura; Uhl, Benjamin (Mitteilungen des Deutschen Germanistenverbandes)

Large-data solutions in one-dimensional thermoviscoelasticity involving temperature-dependent viscosities - Winkler, Michael (Zeitschrift für angewandte Mathematik und Physik)
Abstract An initial-boundary value problem for $$\begin{aligned} \left\{ \begin{array}{ll}u_{tt} = \big (\gamma (\Theta ) u_{xt}\big )_x + au_{xx} - \big (f(\Theta )\big )_x, \qquad & x\in \Omega , \ t>0, \\[1mm] \Theta _t = \Theta _{xx} + \gamma (\Theta ) u_{xt}^2 - f(\Theta ) u_{xt}, \qquad & x\in \Omega , \ t>0, \end{array} \right. \end{aligned}$$ u tt = ( γ ( Θ ) u xt ) x + a u xx - ( f ( Θ ) ) x , x ∈ Ω , t > 0 , [ 1 m m ] Θ t = Θ xx + γ ( Θ ) u xt 2 - f ( Θ ) u xt , x ∈ Ω , t > 0 , is considered in an open bounded real interval $$\Omega $$ Ω . Under the assumption that $$\gamma \in C^0([0,\infty ))$$ γ ∈ C 0 ( [ 0 , ∞ ) ) and $$f\in C^0([0,\infty ))$$ f ∈ C 0 ( [ 0 , ∞ ) ) are such that $$f(0)=0$$ f ( 0 ) = 0 , and $$k_\gamma \le \gamma \le K_\gamma $$ k γ ≤ γ ≤ K γ as well as $$\begin{aligned} |f(\xi )| \le K_f \cdot (\xi +1)^\alpha \qquad \hbox {for all } \xi \ge 0 \end{aligned}$$ | f ( ξ ) | ≤ K f · ( ξ + 1 ) α for all ξ ≥ 0 with some $$k_\gamma>0, K_\gamma>0, K_f>0$$ k γ > 0 , K γ > 0 , K f > 0 and $$\alpha <\frac{3}{2}$$ α < 3 2 , for all suitably regular initial data of arbitrary size a statement on global existence of a global weak solution is derived. By particularly covering the thermodynamically consistent choice $$f\equiv id$$ f ≡ i d of predominant physical relevance, this appears to go beyond previous related literature which seems to either rely on independence of $$\gamma $$ γ on $$\Theta $$ Θ , or to operate on finite time intervals.

Large-data regular solutions in a one-dimensional thermoviscoelastic evolution problem involving temperature-dependent viscosities - Winkler, Michael (Journal of Evolution Equations)
Abstract The model $$\begin{aligned} \left\{ \begin{array}{l}u_{tt} = \big (\gamma (\Theta ) u_{xt}\big )_x + au_{xx} - \big (f(\Theta )\big )_x, \\[1mm] \Theta _t = \Theta _{xx} + \gamma (\Theta ) u_{xt}^2 - f(\Theta ) u_{xt}, \end{array} \right. \end{aligned}$$ u tt = ( γ ( Θ ) u xt ) x + a u xx - ( f ( Θ ) ) x , [ 1 m m ] Θ t = Θ xx + γ ( Θ ) u xt 2 - f ( Θ ) u xt , for thermoviscoelastic evolution in one-dimensional Kelvin–Voigt materials is considered. By means of an approach based on maximal Sobolev regularity theory of scalar parabolic equations, it is shown that if $$\gamma _0>0$$ γ 0 > 0 is fixed, then there exists $$\delta =\delta (\gamma _0)>0$$ δ = δ ( γ 0 ) > 0 with the property that for suitably regular initial data of arbitrary size an associated initial boundary value problem posed in an open bounded interval admits a global classical solution whenever $$\gamma \in C^2([0,\infty ))$$ γ ∈ C 2 ( [ 0 , ∞ ) ) and $$f\in C^2([0,\infty ))$$ f ∈ C 2 ( [ 0 , ∞ ) ) are such that $$f(0)=0$$ f ( 0 ) = 0 and $$|f(\xi )| \le K_f \cdot (\xi +1)^\alpha $$ | f ( ξ ) | ≤ K f · ( ξ + 1 ) α for all $$\xi \ge 0$$ ξ ≥ 0 and some $$K_f>0$$ K f > 0 and $$\alpha <\frac{3}{2}$$ α < 3 2 , and that $$\begin{aligned} \gamma _0 \le \gamma (\xi ) \le \gamma _0 + \delta \qquad \hbox {for all } \xi \ge 0. \end{aligned}$$ γ 0 ≤ γ ( ξ ) ≤ γ 0 + δ for all ξ ≥ 0 . This is supplemented by a statement on global existence of certain strong solutions, particularly continuous in both components, under weaker conditions on the initial data.

Rough solutions in one-dimensional nonlinear thermoelasticity - Winkler, Michael (Calculus of Variations and Partial Differential Equations)
Abstract The hyperbolic-parabolic model $$\begin{aligned} \left\{ \begin{array}{ll} u_{tt} = u_{xx} - \big (f(\Theta )\big )_x, \qquad & x\in \Omega , \ t>0, \\ \Theta _t = \Theta _{xx} - f(\Theta ) u_{xt}, \qquad & x\in \Omega , \ t>0, \end{array} \right. \end{aligned}$$ u tt = u xx - ( f ( Θ ) ) x , x ∈ Ω , t > 0 , Θ t = Θ xx - f ( Θ ) u xt , x ∈ Ω , t > 0 , for the evolution of the displacement variable u and the temperature $$\Theta \ge 0$$ Θ ≥ 0 during thermoelastic interaction in a one-dimensional bounded interval $$\Omega $$ Ω is considered. Whereas the literature has provided comprehensive results on global solutions for sufficiently regular initial data $$(u_0,u_{0t},\Theta _0)=(u,u_t,\Theta )|_{t=0}$$ ( u 0 , u 0 t , Θ 0 ) = ( u , u t , Θ ) | t = 0 when $$f\equiv id$$ f ≡ i d , it seems to have remained open so far how far a solution theory can be built solely on the two fundamental physical principles of energy conservation and entropy nondecrease. The present manuscript addresses this by asserting global existence of weak solutions under assumptions which are energy- and entropy-minimal in the sense of allowing for any initial data $$u_0\in W_0^{1,2}(\Omega )$$ u 0 ∈ W 0 1 , 2 ( Ω ) , $$u_{0t} \in L^2(\Omega )$$ u 0 t ∈ L 2 ( Ω ) and $$0\le \Theta _0\in L^1(\Omega )$$ 0 ≤ Θ 0 ∈ L 1 ( Ω ) , and which apply to arbitrary $$f\in C^1([0,\infty ))$$ f ∈ C 1 ( [ 0 , ∞ ) ) with $$f(0)=0$$ f ( 0 ) = 0 and $$f'>0$$ f ′ > 0 on $$[0,\infty )$$ [ 0 , ∞ ) .

Behavioral effects in human-machine and human-human interactions - Protte, Marius
Diese Dissertation untersucht, wie Menschen Entscheidungen in Interaktionen sowohl mit anderen Personen als auch mit zunehmend verbreiteten algorithmischen Systemen treffen. Unter Einbezug von Erkenntnissen aus der Verhaltensökonomie und der Mensch-Maschine-Interaktion wird analysiert, wie kognitive Limitationen, soziale Präferenzen und Wahrnehmungsverzerrungen das Verhalten in Kontexten von Unehrlichkeit, Empfehlungsumsetzung, Feedbackverarbeitung und Selbsteinschätzung prägen. Vier kontrollierte ökonomische Experimente zeigen, dass algorithmische Intransparenz unehrliches Verhalten verstärken kann, die Einbindung von Nutzern in das Training von KI-Systemen zwar deren Wahrnehmung verbessert, jedoch nicht die tatsächliche Befolgung algorithmischer Ratschläge fördert, dass Echtzeit-Feedback in Human-in-the-Loop-Systemen unbeabsichtigt Verhaltensverzerrungen verstärken kann und dass gängige Messungen von Selbstüberschätzung stark von methodischen Designentscheidungen abhängen. Die Dissertation unterstreicht die Notwendigkeit, realistische Annahmen über menschliches Verhalten bei der Gestaltung von Prüfungsprozessen, Empfehlungssystemen und interaktiven Technologien zu berücksichtigen und leistet damit einen Beitrag zu einem besseren Verständnis menschlicher Entscheidungsprozesse in einer zunehmend automatisierten Welt.

Implementation and Results of a Multi-Stage Model Predictive Traffic Light Control System - Malena, Kevin; Link, Christopher; Gausemeier, Sandra; Trächtler, Ansgar (2024 IEEE 27th International Conference on Intelligent Transportation Systems (ITSC))
This paper deals with the implementation and results of the application of a multi-stage traffic light control system which includes a simulation-based traffic estimation and model predictive control. The traffic light control system incorporates a fuzzy system for traffic light phase preselection, followed by a model predictive control to optimise phase combinations and switching times. Predefined phases are selected without restrictions in the order according to a multi-objective optimisation to adapt to the traffic as freely as possible. Initially, the system is tested in simulations and compared with existing methods and analysed afterwards for its effectiveness in a prototype commissioning in field tests. Results indicate high potentials for reducing emissions and waiting times, highlighting the system's value. However, further refinement is necessary for standard implementation. This comprehensive approach demonstrates advancements in traffic management technology, showcasing the potential for enhancing urban mobility and reducing environmental impact.
Keywords: MPC

Zum Verhältnis von nachhaltigkeitsbezogener Transparenz und strategischem Sichtbarkeitsmanagement - Rossmann, Felix (Jahrbuch Normative und institutionelle Grundfragen der Ökonomik)

Forschungsperspektiven zu Sustainable Finance in kleinen und mittleren Unternehmen - Rossmann, Felix Konstantin (ZfKE – Zeitschrift für KMU und Entrepreneurship)

A Two-Stage Approximation Methodology for Efficient DNN Hardware Implementation - Hadipour, Amir Hossein; Jafari, Atousa; Awais, Muhammad; Platzner, Marco (2025 IEEE 28th International Symposium on Design and Diagnostics of Electronic Circuits and Systems (DDECS))

Broadband Nyquist Pulse Generation on TFLN Platform for Integrated Quantum Source - Kress, Christian; Mihaylov, Martin Miroslavov; Schwabe, Tobias; Silberhorn, Christine; Scheytt, J. Christoph (PIERS Proceedings)
The generation of optically broadband Nyquist pulse sequences using an integrated Mach-Zehnder modulator (MZM) in a thin-film lithium-niobate (TFLN) platform with repetition rates of 5 to 32 GHz and optical bandwidths of up to 160 GHz is demonstrated. Nyquist pulse sequences with high optical bandwidth can be used as synchronization and control signals in quantum sources based on photon pair generation.

Beforschung eines MINT Clusters – erste Ergebnisse und weitere Schritte - Reckmann, Eileen; Temmen, Katrin

Revisiting the analysis of references among Common Criteria certified products - Janovsky, Adam; Chmielewski, Łukasz; Svenda, Petr; Jancar, Jan; Matyas, Vashek (Computers & Security)

ROCA and Minerva Vulnerabilities - JANCAR, Jan; SVENDA, Petr; SYS, Marek (Embedded Cryptography 3)

Let’s DOIT: Using Intel’s Extended HW/SW Contract for Secure Compilation of Crypto Code - Arranz-Olmos, Santiago; Barthe, Gilles; Grégoire, Benjamin; Jancar, Jan; Laporte, Vincent; Oliveira, Tiago; Schwabe, Peter (IACR Transactions on Cryptographic Hardware and Embedded Systems)
It is a widely accepted standard practice to implement cryptographic software so that secret inputs do not influence the cycle count. Software following this paradigm is often referred to as “constant-time” software and typically involves following three rules: 1) never branch on a secret-dependent condition, 2) never access memory at a secret-dependent location, and 3) avoid variable-time arithmetic operations on secret data. The third rule requires knowledge about such variable-time arithmetic instructions, or vice versa, which operations are safe to use on secret inputs. For a long time, this knowledge was based on either documentation or microbenchmarks, but critically, there were never any guarantees for future microarchitectures. This changed with the introduction of the data-operand-independent-timing (DOIT) mode on Intel CPUs and, to some extent, the data-independent-timing (DIT) mode on Arm CPUs. Both Intel and Arm document a subset of their respective instruction sets that are intended to leak no information about their inputs through timing, even on future microarchitectures if the CPU is set to run in a dedicated DOIT (or DIT) mode.In this paper, we present a principled solution that leverages DOIT to enable cryptographic software that is future-proof constant-time, in the sense that it ensures that only instructions from the DOIT subset are used to operate on secret data, even during speculative execution after a mispredicted branch or function return location. For this solution, we build on top of existing security type systems in the Jasmin framework for high-assurance cryptography.We then use our solution to evaluate the extent to which existing cryptographic software built to be “constant-time” is already secure in this stricter paradigm implied by DOIT and what the performance impact is to move from constant-time to future-proof constant-time.

ECTester: Reverse-engineering side-channel countermeasures of ECC implementations - Suchanek, Vojtech; Jancar, Jan; Kvapil, Jan; Svenda, Petr; Chmielewski, Łukasz (IACR Transactions on Cryptographic Hardware and Embedded Systems)
Developers implementing elliptic curve cryptography (ECC) face a wide range of implementation choices created by decades of research into elliptic curves. The literature on elliptic curves offers a plethora of curve models, scalar multipliers, and addition formulas, but this comes with the price of enabling attacks to also use the rich structure of these techniques. Navigating through this area is not an easy task and developers often obscure their choices, especially in black-box hardware implementations. Since side-channel attackers rely on the knowledge of the implementation details, reverse engineering becomes a crucial part of attacks.This work presents ECTester – a tool for testing black-box ECC implementations. Through various test suites, ECTester observes the behavior of the target implementation against known attacks but also non-standard inputs and elliptic curve parameters. We analyze popular ECC libraries and smartcards and show that some libraries and most smartcards do not check the order of the input points and improperly handle the infinity point. Based on these observations, we design new techniques for reverse engineering scalar randomization countermeasures that are able to distinguish between group scalar randomization, additive, multiplicative or Euclidean splitting. Our techniques do not require side-channel measurements; they only require the ability to set custom domain parameters, and are able to extract not only the size but also the exact value of the random mask used. Using the techniques, we successfully reverse-engineered the countermeasures on 13 cryptographic smartcards from 5 major manufacturers – all but one we tested on. Finally, we discuss what mitigations can be applied to prevent such reverse engineering, and whether it is possible at all.

On the complexity of estimating ground state entanglement and free energy - Gharibian, Sevag; Kamminga, Jonas (arXiv:2510.06796)
Understanding the entanglement structure of local Hamiltonian ground spaces is a physically motivated problem, with applications ranging from tensor network design to quantum error-correcting codes. To this end, we study the complexity of estimating ground state entanglement, and more generally entropy estimation for low energy states and Gibbs states. We find, in particular, that the classes qq-QAM [Kobayashi, le Gall, Nishimura, SICOMP 2019] (a quantum analogue of public-coin AM) and QMA(2) (QMA with unentangled proofs) play a crucial role for such problems, showing: (1) Detecting a high-entanglement ground state is qq-QAM-complete, (2) computing an additive error approximation to the Helmholtz free energy (equivalently, a multiplicative error approximation to the partition function) is in qq-QAM, (3) detecting a low-entanglement ground state is QMA(2)-hard, and (4) detecting low energy states which are close to product states can range from QMA-complete to QMA(2)-complete. Our results make progress on an open question of [Bravyi, Chowdhury, Gosset and Wocjan, Nature Physics 2022] on free energy, and yield the first QMA(2)-complete Hamiltonian problem using local Hamiltonians (cf. the sparse QMA(2)-complete Hamiltonian problem of [Chailloux, Sattath, CCC 2012]).

Understanding personal agency through metaphor, or Why academic writing is (not) like a roller-coaster ride - Karsten, Andrea (Frontiers in Language Sciences)
Building on and methodologically extending conceptual metaphor theory, the article examines how personal agency as a discursively produced sociopsychological phenomenon can be studied in elicited metaphors through a discourse-analytical approach. More concretely, the study illustrates how early-career researchers experience and express their agency in research writing through personal metaphors of academic writing such as riding a roller coaster or baking a wedding cake. A two-step discursive analysis adapts Hopper and Thompson's multidimensional approach to linguistic transitivity to study agency in language. The analytical approach involves both an in-depth parametrized analysis of all metaphors in the sample and a qualitative cross-analysis of the data. The results show that the participants' metaphors reflect both nuanced personal experiences and cultural expectations of academic writing, the writer, and the text. This emphasizes that research writing is not only a highly subjective practice but also one that is socially and culturally influenced. The article argues that research on agency thus needs elaborate methodological tools to trace discursive and sociopsychological trajectories of complex socio-cognitive practices like academic writing. This has implications not only for the nexus of research writing, identity, and academic enculturation but also for other fields focusing on agency in language.

Annotation Schemes Project A02 "Monitoring the understanding of explanations" - Lazarov, Stefan Teodorov; Türk, Olcay; Grimminger, Angela; Wagner, Petra; Buschmeier, Hendrik

Understanding personal agency through metaphor, or Why academic writing is (not) like a roller-coaster ride - Karsten, Andrea Ramona (Frontiers in Language Sciences)
Building on and methodologically extending conceptual metaphor theory, the article examines how personal agency as a discursively produced sociopsychological phenomenon can be studied in elicited metaphors through a discourse-analytical approach. More concretely, the study illustrates how early-career researchers experience and express their agency in research writing through personal metaphors of academic writing such as riding a roller coaster or baking a wedding cake. A two-step discursive analysis adapts Hopper and Thompson's multidimensional approach to linguistic transitivity to study agency in language. The analytical approach involves both an in-depth parametrized analysis of all metaphors in the sample and a qualitative cross-analysis of the data. The results show that the participants' metaphors reflect both nuanced personal experiences and cultural expectations of academic writing, the writer, and the text. This emphasizes that research writing is not only a highly subjective practice but also one that is socially and culturally influenced. The article argues that research on agency thus needs elaborate methodological tools to trace discursive and sociopsychological trajectories of complex socio-cognitive practices like academic writing. This has implications not only for the nexus of research writing, identity, and academic enculturation but also for other fields focusing on agency in language.